Changes in analytical and volatile compositions of red wines induced by pre-fermentation heat treatment of grapes. (15th November 2015) - Geffroy, Olivier; Lopez, Ricardo; Serrano, Eric; Dufourcq, Thierry; Gracia-Moreno, Elisa; Cacho, Juan; Ferreira, Vicente
Highlights: We studied the impact of prefermentation heat treatment of grapes on red wine characteristics. Results suggest thermal degradation of terpenols, norisoprenoids and phenols. Wines fermented in liquid phase has greater concentrations in ethyl esters, acetates and fatty acids. For this treatment, we showed large gains in the amino acid composition of the must. The aroma composition of wines fermented in solid phase was more similar to those of the control vinification. Abstract: Experiments were carried out on Grenache, Carignan and Fer grapes in order to characterize the changes in nitrogen content of the musts, conventional enological parameters and aroma compounds of the wines induced by pre-fermentation heating of the grapes followed by alcoholic fermentation in liquid phase or in solid phase. In comparison to a standard vinification, we showed that a two-hour heat treatment at 70 °C induced a significant loss in several grape-derived aroma compounds (terpenols, norisoprenoids and some phenols) associated with an increase in α-terpineol, guaiacol and 2, 6-dimethoxyphenol, which suggests thermal degradation. A significant increase in most of the ethyl esters, in acetates and in fatty acids were observed in wines fermented in liquid phase, together with a decrease in fusel alcohols. The substantial modification in the amino acid composition of the must seems to be a crucial element for the understanding of these changes.